Papilomavirus Humano (HPV) - Um estudo de revisao - Soares, Christiane Pienna [UNESP] (My University, 1999)
Human Papillomaviruses (HPVs) are epitheliotropic viruses, that induce benign and malignant lesions on several body sites. It's a small circular DNA virus, non-enveloped and 75 types have been identified. Frequently HPV 6, 11 (benign lesions) and 16, 18 (malignant lesions) are occurred on mucosa. The infection takes place at the basal layer cells with microlesions, when the virus enters into the cells and looses the capsid. The benign HPV types is associated to cell's genome in epissomal way. In malignant lesions, it integrates into the cell's DNA. HPV viruses are sexually transmitted and responsable for malignant cell transformation. Thus this viruses have an extremely epidemiologic importance. This paper reports a HPV review study about: epidemiology, diagnostic methods and treatment to papillomavirus infection.
Human Papillomavirus (HPV) - A review
Keywords: Diagnostic methods; Epidemiology; Human papillomavirus; Treatment; alpha interferon; antivirus agent; cidofovir; fluorouracil; imiquimod; podophyllin; podophyllotoxin; virus vaccine; antibiotic therapy; cryotherapy; diagnostic approach route; electrosurgery; laser surgery; malignant transformation; review; verruca vulgaris; virion; virus carcinogenesis; virus characterization; virus genome; virus infectivity; virus transmission; Wart virus